Entrepreneurship, Innovations and The Firms - Chee, Kok Wah (2008)
The AIDs and the SARs epidemics had spurred the growth of the glove industry. However, due to competition, the number of glove manufacturers had reduced from 200 during the boom in the late 1980s to 40 at present. During the span of history from the boom to present, major events such as the FDA stringent requirements, the rise of commodity prices and shortage of labour had impacted the glove industry tremendously. The survivals of these firms were no accidental but due to the firms’ entrepreneurship and innovations. Firms that were innovative and have sustainable competitive advantage continues to enjoy growth as the worlds’ demand of gloves continue to grow at 10% per annum while less competitive firms exit the industry. Through systematic process of examining literatures in transaction cost economics and strategic management, developing a conceptual framework, selection of appropriate methodology and analysis of cases, the research questions pertaining to the survival and growth of these firms had been addressed. The research findings showed close relationships between the entrepreneurship, innovations and firm strategies. These factors are crucial to the survival and growth of the firms.